The transformative power of mentorship on novice teacher success: a recent systematic literature review (2022-2024) - Ping Jin, Beranda Yii; Md Zalli, Mohd Muslim; Mohd Jamil, Mohd Ridhuan; Hanis, Nik Muhammad; Ambon, Josephine (Institute of Advanced Engineering and Science, 2025)
This study examines the transformative impact of mentorship in building resilience and enhancing success among novice teachers. By identifying effective mentorship strategies and frameworks, the research addresses critical early-career challenges, supports teacher retention, and contributes to the global aim of quality education. Using a systematic literature review (SLR) guided by preferred reporting items for systematic reviews and meta-analyses (PRISMA) methodology, the study analyzed 45 articles from Scopus and ERIC databases, covering publications from 2022 to 2024. Through qualitative thematic analysis, three main themes emerged: emotional and psychological support in mentoring, mentoring models and professional development frameworks, and cultural and contextual influences on mentoring. Findings suggest that mentorship is pivotal in helping novice teachers navigate stress, improve instructional skills, and adapt to diverse school environments. Limitations include the restricted scope to select databases, potentially omitting other relevant studies. Future research could broaden the literature base and assess mentoring’s long-term impacts across varied educational contexts. This study contributes to the field by highlighting mentorship’s essential role in fostering resilience among novice teachers, aligning with sustainable development goal 4 (SDG 4) to promote teacher retention and educational quality.